Intro to alien invasion - King, Owen; Poirier, Mark Jude (Scribner, 2015)
"Stacey, a brilliant, overachieving astrobiology major at Fenton College, had planned on just another lonely spring break on campus. But when a hurricane batters the small college town, downing power lines and knocking out cell phone reception, Stacey and her friends are stranded with no way to communicate with the outside world at the worst possible moment: in the midst of an alien invasion. As space insects begin to burrow into students and staff, transforming them into slobbering, babbling monsters, a conglomeration of misfits must band together to prevent the infestation from spreading. Meanwhile, Stacey's long-stifled romantic feelings for her friend Charlotte begin to surface, while the professor she had admired and respected becomes the students' worst enemy" --